Impact of the Covid-19 Pandemic on the Stock Market in Indonesia - Herlina Lubis; M. Ikhsan Harahap (Universitas Muhammadiyah Enrekang, 2022)
This study aims to elaborate the shock of the stock market in early stage of Covid-19 pandemic. Indonesia’s condition which is currrently being hit by the Covid-19 pandemic affects the stock market and economic growth. Composite index has decreased as well as economic growth. This study uses a descriptive exploratory method, secondary data collected from BEI and Bappenas RI. The results of the study show that there has been a decline of share prices in all industrial sectors. The worst decline was in the property sector (-33,32%) and the lightest decline was in the consumer goods (-9,96%). Based on the results, recommendations were obtained for the government to accelerate stock market stability by increasing the number of aid recipients in the UMKM sector, conducting more intensive socialization regarding the dangerous and prevention of Covid-19, and providing relief to issuers who have loans; recommendations for issuers to maintain company performance by keeping employes from being infected from Covid-19 invection, maintaining employee performance, applying online technology in all fields; and recommendations for investors to implement the best strategy for investing by conducting fundamental and technical analysis, making the stock portfolios, selecting the business sectors, and looking for the latest information about issuers